Behold the lilies: Martin Buber and the contemplation of nature1. Issue 1 (6th March 2018) - Santmire, H. Paul
Abstract: Christians attuned to ecological and eco‐justice issues typically welcome the thought that they are called by God to protect and to serve nature, as well as to respond to the needs of the poor and the oppressed. Drawing on Martin Buber's I‐Thou and I‐It conceptuality and highlighting Jesus' command about the lilies of the field, this article argues that Christians also are called to enter into an I‐Ens relationship with nature, that is, to behold or to contemplate, as well as to protect and to serve nature, as they continue to address ecojustice issues.